Mathematics

Please help?

An equation is shown below:

4(x - 3) - 5(x + 1) = 3

Which statement shows a correct next step in solving the equation?

The equation can become 4x - 3 - 5x + 1 = 3 by applying the associative property of multiplication.

The equation can become 4x - 3 - 5x + 1 = 3 by applying the distributive property.

The equation can become 4x - 12 - 5x - 5 = 3 by applying the distributive property.

The equation can become 4x - 12 - 5x - 5 = 3 by applying the associative property of multiplication.


Answers

Peanut2

2 years ago Comment

To solve an equation, it is important to follow the basic rule of PEMDAS. We are given the equation:

4(x - 3) - 5(x + 1) = 3

Following the rule, we have to distribute first the numbers 4 and 5 into the expressions inside the parentheses. Therefore, the correct answer from the choices listed is option 3. The equation can become 4x - 12 - 5x - 5 = 3 by applying the distributive property.